THE INFLUENCE OF THE NUMBER OF LEAVES IN THE MACAÚBA PALM Acrocomia aculeata (Jacq.) Lodd. ex Mart. ON THE CORRELATION BETWEEN STEMFLOW AND GROSS PRECIPITATION - João Batista Lúcio Corrêa; Herly Carlos Teixeira Dias; Aurora Yoshiko Sato; Kelly Cristina Tonello; Alexandre Gomes Ferraz; Filipe Manoel Ferreira (Revista Árvore)
ABSTRACT The macaúba palm (Acrocomia aculeata) has a great production potential of oil and is an important alternative to diversify agricultural production. In view of the hypothesis that the species may provide a positive contribution to the hydrological processes in a watershed, we aimed to assess the influence of the number of leaves per macaúba plant on the correlation between stemflow and gross precipitation. We installed three rain gauges to monitor gross precipitation in an experimental area, and stemflow collectors on the stem of eight macaúba plants therein having 10, 13, 18, and 22 leaves. Linear regression equations were obtained, which enabled us to estimate the minimum rainfall volume required for the occurrence of stemflow. A strong positive linear correlation was observed between stemflow and gross precipitation, regardless of the number of leaves per plant. The morphological characteristics of the macaúba palm favor rainfall interception, relatively high stemflow values being shown even in young plants. The funnel-shaped crown enabled the conduction of large rainfall volumes to the stem, thus resulting in the occurrence of stemflow even with light precipitations.